2014
DOI: 10.1016/j.jmb.2013.12.014
|View full text |Cite
|
Sign up to set email alerts
|

APOBEC3 Multimerization Correlates with HIV-1 Packaging and Restriction Activity in Living Cells

Abstract: APOBEC3G belongs to a family of DNA cytosine deaminases that are involved in the restriction of a broad number of retroviruses including HIV-1. Prior studies have identified two distinct mechanistic steps in Vif-deficient HIV-1 restriction: packaging into virions and deaminating viral cDNA. APOBEC3A, for example, although highly active, is not packaged and is therefore not restrictive. APOBEC3G, on the other hand, although having weaker enzymatic activity, is packaged into virions and is strongly restrictive. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
88
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 67 publications
(98 citation statements)
references
References 95 publications
10
88
0
Order By: Relevance
“…Furthermore, in an in vitro RT model system, the presence of APOBEC3C cause a higher mutation frequency than APOBEC3C S188. A previous study correlated multimerization of APOBEC3s with the capacity to restrict lentiviruses [51], and our finding that the monomeric variant (S188) was less antivirally active than the dimer-forming, more active variant (I188), is consistent with this conclusion. Therefore, our model is that isoleucine at position 188 of APOBEC3C enhances lentiviral restriction by improving dimerization and in turn, the enzymatic activity of the protein.…”
Section: Mechanism Of Increased Activity Of Apobec3c I188 Relative Tosupporting
confidence: 91%
See 3 more Smart Citations
“…Furthermore, in an in vitro RT model system, the presence of APOBEC3C cause a higher mutation frequency than APOBEC3C S188. A previous study correlated multimerization of APOBEC3s with the capacity to restrict lentiviruses [51], and our finding that the monomeric variant (S188) was less antivirally active than the dimer-forming, more active variant (I188), is consistent with this conclusion. Therefore, our model is that isoleucine at position 188 of APOBEC3C enhances lentiviral restriction by improving dimerization and in turn, the enzymatic activity of the protein.…”
Section: Mechanism Of Increased Activity Of Apobec3c I188 Relative Tosupporting
confidence: 91%
“…Previous studies have reported that the S188 variant of APOBEC3C is a monomeric protein, both in solution [149] and in cells [51]. Indeed, by size exclusion chromatography we also found that baculovirus/Sf9-produced APOBEC3C S188 (the common variant) is monomeric ( Figure 3.7A, apparent molecular weight 17 kDa).…”
Section: Dimerization Correlates With Enhanced Antiviral Activity Ofsupporting
confidence: 72%
See 2 more Smart Citations
“…1D). Our data combine to indicate that the A3Bctd is active as a monomer, although we have not addressed the possibility that it might oligomerize upon substrate engagement, and it is notable that full-length protein is capable of forming higher order oligomers in a cellular context, most likely through its insoluble N-terminal domain (54). Closed Conformation of the A3B Active Site-In the structure of A3Bctd-QM⌬loop3, a single zinc ion is bound between the N-terminal ends of ␣2 and ␣3, coordinated by two cysteines (Cys-284 and Cys-289) and a histidine (His-253; Fig.…”
Section: Resultsmentioning
confidence: 79%